게임스토리에 나타난 영웅의 모험(Hero's Journey)의 12가지 단계 분석 - 노창현(Chang-Hyun Roh); 이완복(Wan-Bok Lee) (한국콘텐츠학회 논문지, 6(11), 2006)
Recently, embedding method of a story into a game has gathered much attention than ever. In this study, the 12 phases of Hero's Journey, which was suggested by Joseph Campbell and was highlighted in the area of movies and myths, has been analysed at a point of Christoper Vogler. Since a gamer is not just only a player but also a story-teller in a game, the story experienced by the player enjoying the game was examined and correlated with the 12 phases of Campbell. The game RCT3, a construction/management simulation game ,produced by Atari, was studied. The 12 phases of Campbell was applicable to game story. 최근 들어 게임에 스토리를 접목하는 방법에 대한 관심이 증대되고 있다. 본 연구에서는 영화와 신화에서 주목받았던 조셉 켐벨(Joseph Campbell)의 영웅의 모험(Hero's Journey)에 등장하는 12가지 단계를 크리스토퍼 보글러(Christoper Vogler)의 관점에서 분석하고 게임과 어떻게 연관될 수 있는지 조사하였다. 게임에서 게이머는 주인공의 분신인 동시에 스토리텔러에 해당하기 때문에 게이머는 게임을 장시간 즐기는 과정에서 스토리를 만들어 나가게 된다. 게임에서 만들어 질 수 있는 스토리 구조를 분석하여 켐벨의 12가지 단계와 관계성을 연구하였다. 아타리(Atari)사에서 출시한 건설경영시뮬레이션 게임인 RCT3를 연구대상으로 하였다. 연구결과 켐벨의 12가지 단계는 게임스토리에 상당부분 적용이 가능했다.